Management of contact dermatitis due to nickel allergy: an update - Fernanda Torres1; Maria das Graças Mota Melo2; Antonella Tosti3 (Dove Medical Press, 2009)
Fernanda Torres1, Maria das Graças Mota Melo2, Antonella Tosti31Department of Dermatology, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 2Occupational Dermatology Sector, Center for the Study of Worker Health and Human Ecology, National School of Public Health, FIOCRUZ, Rio de Janeiro, Brazil; 3Department of Dermatology, University of Bologna, Bologna, ItalyAbstract: Nickel is the major cause of allergic contact dermatitis in the general population, both among children and adults, as well as in large occupational groups. This metal is used in numerous industrial and consumer products, including stainless steel, magnets, metal plating, coinage, and special alloys, and is therefore almost impossible to completely avoid in daily life. Nickel contact dermatitis can represent an important morbidity, particularly in patients with chronic hand eczema, which can lead to inability to work, a decrease in quality of life and significant healthcare expenses. Therefore, its management is of great importance. This article reviews diagnostic, preventive and therapeutic strategies in this field.Keywords: allergic contact dermatitis, metals, contact hypersensitivity, occupational exposure, children, contact dermatitis